Short-chain fatty acid formation in the hindgut of rats fed oligosaccharides varying in monomeric composition, degree of polymerisation and solubility - Nilsson, Ulf; Nyman, Margareta (British journal of nutrition, 2005)
The contents of short-chain fatty acids were investigated in rats fed lactitol, lactulose and four fructo-oligosaccharides of different degree of polymerisation and solubility. Fructo-oligosaccharides with a low degree of polymerisation (2–8) generated the highest levels of butyric acid all along the hindgut, whereas fructo-oligosaccharides with a high degree of polymerisation (10–60) generated the highest levels of propionic acid. These specific differences were also generally reflected in the caecal pools and molar proportions of short-chain fatty acids. The lower solubility of the fructo-oligosaccharides was related to a lower degree of caecal fermentation. Lactulose and lactitol yielded high proportions of acetic acid and low proportions of butyric acid. It is concluded that both the degree of polymerisation and the solubility may affect short-chain fatty acid formation, whereas the fructose content per se seem to be of less importance. This may be of interest when designing foods with specific health effects.